Pengaruh Facility Support, Service Performance, dan Customer Satisfaction Terhadap Word of Mouth - Jowianto, Markus; Zuhdi, Saefudin (LPPM Institut Bisnis dan Informatika Kesatuan, 2019)
The purpose of this study was to determine how much influence the facility support, service performance and customer satisfaction have on the word of mouth R. S. Sentra Medika Cibinong. The method of analysis in this study uses multiple regression analysis and correlation to test the significance of the relationship between variables with a quantitative approach. The data source of this research is primary data obtained by interview using online questionnaire instruments to 100 respondents. The results of this study indicate that all independent variables have a positive effect on word of mouth. However, customer satisfaction variables that significantly influence word of mouth.Keywords: FACILITY SUPPORT, SERVICE PERFORMANCE, CUSTOMER SATISFACTION, AND WORD OF MOUTH.